2021
DOI: 10.1038/s41598-021-00336-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the formation of two types of oxygen interstitials in neutron-irradiated α-Al2O3 single crystals

Abstract: Due to unique optical/mechanical properties and significant resistance to harsh radiation environments, corundum (α-Al2O3) is considered as a promising candidate material for windows and diagnostics in forthcoming fusion reactors. However, its properties are affected by radiation-induced (predominantly, by fast neutrons) structural defects. In this paper, we analyze thermal stability and recombination kinetics of primary Frenkel defects in anion sublattice − the F-type electronic centers and complementary oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The relationship between the activation energy E a of a certain kinetic process and the pre-exponential X, Equation ( 9), is well known in the chemical literature as the Meyer-Neldel rule [35,36]. In the case of radiation defects, the fulfillment of this relation was confirmed by us for a group of ionic crystals (Al 2 O 3 , MgO, MgF 2 , MgAl 2 O 4 ) [33,37]. Note, however, that in the paper [33] we can talk about proof, since statistics based on a large number of independent experiments were used for each material.…”
Section: Resultsmentioning
confidence: 78%
“…The relationship between the activation energy E a of a certain kinetic process and the pre-exponential X, Equation ( 9), is well known in the chemical literature as the Meyer-Neldel rule [35,36]. In the case of radiation defects, the fulfillment of this relation was confirmed by us for a group of ionic crystals (Al 2 O 3 , MgO, MgF 2 , MgAl 2 O 4 ) [33,37]. Note, however, that in the paper [33] we can talk about proof, since statistics based on a large number of independent experiments were used for each material.…”
Section: Resultsmentioning
confidence: 78%
“…The results obtained by us ( Figure 2 ) clearly indicate the relationship between the decrease in the intensity of the ESR signal of F + -centers at T = 375–550 K and the emission of TL peaks in the indicated temperature range, which confirms the assumption made by the authors of [ 45 , 46 , 47 ]. It is well known that an alternative mechanism for annealing radiation-induced F -type defects in oxides is the recombination of oxygen vacancies with interstitial oxygen, the diffusion of which becomes possible when the crystal is heated [ 48 , 49 , 50 ]. Previously, the authors of [ 51 ] showed that in zirconium oxide irradiated with neutrons (E > 0.1 MeV), the diffusion of interstitial oxygen becomes possible at temperatures above 500–600 K. In the samples studied by us, a decrease in the concentration of F + centers is observed at lower temperatures of 375–550 K, which testifies in favor of the proposed mechanism for the destruction of F + centers associated with their ability to capture the charge carriers released from traps that cause TL peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we come to the final result (see also Refs. [34][35][36][37][38][39]) when the theory can already be compared with experiment.…”
Section: Analysis Of Kineticsmentioning
confidence: 99%